Stress detection using galvanic skin response - Shahnaz Sakinah, Shaiful Bahri (2016)
Galvanic Skin Response (GSR) is a method of measuring electrical conductance of the skin. Strong emotion cause stimulus to sympathetic nervous system, resulting more sweat being secreted by the sweat glands. From the data collected, we will have to analyse the data and graph to know at what point is the subject in stress or not stress. Different subject, different level of stress state depends on their physical and mental balance. Some subjects have strong emotion not only while they are stress, but also when they are very happy, very sad and also nervous. This is also triggered as strong emotion that the GSR sensor will detect any changes of emotion. We also have to see what type of activities that the subject are doing or undergo during the data is recorded. By placing the GSR at any two fingers on one hand, the GSR will start to detect any sweats or strong emotions of the subject. It will run the serial monitor after the Arduino coding is uploaded. The data will be displayed and analysed according to the activities that have been done. The data collected will be transferred to Matlab for further analysis. The graph is plotted from the Matlab for each subject out of 15 subjects. But only 9 subjects is counted. The results and graph are differ for every subjects although they went through the same activities. Every subjects does not have the same physical and mental state before, during and after the activities. Besides that, the amount of sweats secreted by each subject’s body (sweat glands) and their emotion will also affect the data, results and graph. As we observed the subjects and the activities they were undergo, we knew how their emotion at that state was.